How can brands become central in the consumers’ life? - Japutra, A.; Loureiro, S. M. C.; Wang, S.; Primanti, H. (Spanish Journal of Marketing - ESIC, 2023)
Purpose Brand centrality is a religion-like brand–customer relationship, which refers to the extent to which a brand is in the center or heart of a consumer’s life. While its role in the fast fashion industry is prominent, its drivers and effects have not been comprehensively studied. This study aims to investigate the relationships between three psychological drivers (i.e. fashion-conscious, chronic shopping orientation and self-esteem), one behavioral driver (i.e. the average frequency of shopping), brand centrality and relationship quality in the fast fashion industry. Design/methodology/approach A survey of 250 fast fashion consumers was conducted and partial least squares-structural equation modeling (PLS-SEM) was used to analyze the data. Findings The study shows that fashion consciousness and chronic shopping orientation are positively related to brand centrality, whereas self-esteem is negatively related to brand centrality. The findings also show that shopping frequency moderates the relationship between fashion consciousness and brand centrality, and between chronic shopping orientation and brand centrality. Post hoc analysis indicates that brand centrality fully mediates the relationship between chronic shopping orientation and relationship quality. Originality/value This study is one of the first studies to investigate the psychological and behavioral drivers of brand centrality. Objetivo La centralidad de la marca es una relación religiosa entre marca y cliente que se refiere al grado en que una marca está en el centro o corazón de la vida de un consumidor. Aunque su papel en la industria de la moda rápida es destacado, sus impulsores y efectos no se han estudiado exhaustivamente. El presente estudio investiga las relaciones entre tres impulsores psicológicos (la conciencia de la moda, la orientación a las compras crónicas y la autoestima), un impulsor conductual (la frecuencia media de las compras), la centralidad de la marca y la calidad de las relaciones en el sector de la moda rápida. Diseño Se realizó una encuesta a 250 consumidores de moda rápida y se utilizó (PLS-SEM) para analizar los datos. Resultados El estudio muestra que la conciencia de la moda y la orientación a las compras crónicas están positivamente relacionadas con la centralidad de marca, mientras que la autoestima está negativamente relacionada con la centralidad de marca. Los resultados también muestran que la frecuencia de compra modera la relación entre la conciencia de la moda y la centralidad de marca, y entre la orientación de compra crónica y la centralidad de marca. El análisis post-hoc indica que la centralidad de la marca media totalmente la relación entre la orientación a las compras crónicas y la calidad de las relaciones. Originalidad Este estudio es uno de los primeros en investigar los impulsores psicológicos y conductuales de la centralidad de marca.